Regional Decentralization of Purwakarta 2018-2022: Effectiveness And Growth Of Local Original Income - Widiya Avianti (Journal of Accounting Inaba, 2024)
The government provides financial assistance to regions in the form of intergovernmental transfers from the State Budget (APBN) to support decentralisation policies, used to finance regional needs, such as infrastructure development and public services. The aim is to improve the welfare of the local population and enhance local autonomy in decision-making, financial management, and reduce fiscal disparities between the central and local governments, as well as between different regions. The central government delegates sources of financial revenue to the regions to be managed effectively and efficiently, including through regional own-source revenues (PAD), to support regional autonomy and fund its tasks and functions. This qualitative research aims to test and analyse: (1) The effect of local own-source revenue (PAD) effectiveness on fiscal decentralisation in the region. (2) The effect of local own-source revenue (PAD) growth on fiscal decentralisation in the regions. (3) The effect of effectiveness and growth of local own-source revenue (PAD) on fiscal decentralisation in the region. The object of research is the PAD Realisation Report of Purwakarta Regency from 2018 to 2022. The sample consists of five reports, namely the PAD report for the 2018-2022 period. There are three points from the results of this study: (1) PAD effectiveness has no significant influence on fiscal decentralisation in the region (significance value 0.216 > 0.05); (2) PAD growth has no significant influence on fiscal decentralisation, (significance value 0.216 > 0.05); PAD effectiveness and growth have no significant influence on fiscal decentralisation, (significance value 0.385 > 0.05).